Implementation Student Centered Approach in Thematic Learning in Elementary School - Subhan, Nur Ali (Journal of Blended and Technical Education, 2025)
Objective: This study aims to explore the application of the Student-Centered Approach (SCA) in thematic learning at the primary school level, particularly within the framework of the Merdeka Curriculum in Indonesia, to address literacy challenges and promote holistic student development. Research Design & Methods: This research uses a descriptive qualitative method with a library approach to various literature, scientific journals, research articles, books, conference proceedings, and case studies of SCA-based thematic learning implementation in elementary schools in Indonesia. Findings: The results indicate that implementing SCA in thematic learning can enhance student engagement, critical thinking skills, learning motivation, and overall learning outcomes. Various SCA models, such as collaborative learning, design thinking, game-based learning, tactical approach, and flipped classroom, enrich students' learning experience with a more meaningful and contextual approach. Implications & Recommendations: The integration of SCA in thematic learning needs to be supported through teacher training, curriculum flexibility, and the development of learning support facilities. Policy makers and school leaders are expected to create an educational ecosystem that supports the adoption of innovative and student-centered pedagogical approaches. Contribution & Value Added: This article contributes to the discourse on education reform in Indonesia by highlighting the strategic role of SCA in improving literacy and supporting the objectives of the Merdeka Curriculum. It provides a conceptual framework for enhancing the quality of basic education through student-centered, thematic learning.